Co-combustion of residual forest biomass and sludge in a pilot-scale bubbling fluidized bed. (10th March 2020) - Pio, D.T.; Tarelho, L.A.C.; Nunes, T.F.V.; Baptista, M.F.; Matos, M.A.A.
Abstract: In this work, the co-combustion of residual forest biomass from eucalyptus and its blend with different amounts of primary and secondary sludge from the pulp and paper industry was studied in a pilot-scale bubbling fluidized bed reactor. The main objective was the determination of sludge addition influence on the overall process and on the composition of the exhaust gases, with emphasis on chlorine emissions, namely present in the solid phase (fly ashes) and in the gaseous phase (hydrogen chloride), and nitrogen oxides emissions. The co-combustion process of residual forest biomass with primary sludge (up to 5% in mass) and secondary sludge (up to 10% in mass) was successfully demonstrated as a valid energy valorization option. Except specific cases, no significant emissions increase of nitrogen oxides, carbon monoxide or hydrogen chloride were found with the addition of sludge. In fact, hydrogen chloride emissions decreased, potentially due to an increase in the chlorine retention in ashes caused by the high inorganic content present in the sludge. This high inorganic content can also lead to a significant increase in ash production during the combustion process. Thus, consequently, without proper maintenance, significant ash accumulation along the combustion system may occur, which can decrease the process efficiency and cause equipment damage. Highlights: Co-combustion of residual forest biomass and sludge is shown as a valid valorization option. Process stability was attained and demonstrated. NO, CO and HCl emissions did not increase with sludge addition.